Is the halo effect universal? An investigation of the generalizability and applications of the halo effect - Gabrieli, Giulio (Nanyang Technological University, 2022)
The influence of the perception of a single trait, such as the aesthetic appearance, on the global evaluation of a person is a phenomenon widely investigated in social psychology. Mostly defined as Halo Effect, this phenomenon has been deeply studied for more than a hundred years now, and findings such as the relationship between aesthetic appearance and other personality traits like competence and trustworthiness have since been uncovered. The latter plays an especially crucial role in individuals’ social interactions. Despite the large body of literature published on the Halo Effect, and especially on the relationship between aesthetic appearance and perceived trustworthiness, little is known about the overall generalizability of the effect. Almost all of the studies have been conducted on adult participants from western countries. Moreover, nothing is known about the stability of the effect over time, in the event of major destabilization, such as a new pandemic outbreak. In this work, the cross-cultural generalizability of the Halo Effect is investigated, as well as its stability over time and its explotability. Six different studies on the Halo Effect are here reported. In chapter 3, a comparison of the evaluation of participants of two different ethnic groups —Asian and Caucasian— toward individuals of their ethnic ingroup or outgroup is made. Additionally, the variations in the intensity of the Halo in adults and children are investigated. In chapter 4, the differences between two different Halo Effects (Liking times Trustworthiness and Aesthetic × Trustworthiness) are investigated. In chapter 5, the time-evolution changes of the strength of the Halo Effect during the recent SARS-CoV-2 pandemic outbreak are investigated, to study the stability of the effect over time. Chapter 6 investigates how the usage of a Prime that promotes more or less contact with others influence 9 the Halo Effect’s stability, while chapter 7 investigates the stability affected by a change in the aesthetic appearance of strangers, induced by face mask wearing. Finally, chapter 8 investigates the exploitability of the Halo Effect of faces, by employing them as tools to increase the perceived Trustworthiness of an Automated Teller Machine (ATM) Taken together, the results of the six studies confirm that the effect extends across individuals of different cultures, but not across individuals of different ages. Significant differences have in fact been found in the strength of the relationship between adults and children. Additionally, the effect has been proven to be affected by external events, such as the SARS-CoV-2 outbreak, with a fast return to the baseline level. Results from chapter 5, 6, and 7 confirm the instability of the effect over time, while results of chapter 8 suggests that faces can be exploited to increase the perceived Trustworthiness of objects. Overall, the findings support the effect’s theoretical underpinnings and uniformity in adults, the uniqueness of children’s faces, and the opportunity of using the effect to improve perceived traits such as trustworthiness.